REDESIGN SHORE PROTECTION KAWASAN INDUSTRI KENDAL (KIK) - Fachri Fatkhur Rizal; Endro Sulistriono; Totok Apriyanto; Ratih Pujiastuti (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2024)
Abrasion incidents on the coastline in the KIK area continue to occur and cause the area boundaries to decline. so that appropriate coastal protection structures are needed. The aim of this research is to carry out re-planning in the Kendal Industrial Area (KIK) in the future area boundary plan. In carrying out this research, daily wind data for the period 2017 - 2023 is needed from a nearby location, namely the Tanjung Emas Maritime Meteorological Station, Semarang. The analysis carried out includes fetch, windrose, wave calculations, building design and force calculations in shore protection construction. From the results of the windrose analysis, the dominant wave direction is northwest. Analysis of waves in the deep sea obtained a height value of 2.45 m and a wave period of 8.32 sec. Based on the calculation results, breaking waves will occur at a depth of 2.02 m. Because the building location is at a depth of 2m, where breaking waves occur, the breaking wave height is used in building planning. The coastal protection building chosen is shore protection construction or a tetrapod sea wall. Peak elevation of 4.76 meters, peak width of 3.55 meters, building base length of 22.45 meters, back slope of 1:1, arm slope of 1:2, the first type of protective layer material uses tetrapods, second and third layer using split stone pairs with 2 size combinations.